Not the Time for Central Bank Digital Currency - Ansgar Belke; Edoardo Beretta (Credit and Capital Markets – Kredit und Kapital, 2020)
This short article addresses several important (but less discussed) aspects of the introduction of central bank digital currency that give cause for concern, no matter whether such a currency is intended as a substitute or a complement to cash. It discusses potential effects, such as bank runs and capital flight, and analyzes possible interactions between central bank digital currency and the limits on cash payments that already exist in several European countries. What are the structural characteristics that still make paper money and coins (the only means of payment directly issued by central banks) irreplaceable? These and other issues (including effects of COVID-19 on cash payment limits) are explored through a discursive approach that is simultaneously grounded in rigorous macroeconomic analysis.
Keywords: E51; E58; E71; 330; Cash Transaction Limits; Central Bank Digital Currency; Payment Systems